RELATIONSHIP BETWEEN SEA SURFACE TEMPERATURE AND CHLOROPHYLL-A WITH YELLOWFIN TUNA CATCH AT THE CILACAP OCEAN FISHING PORT, INDONESIA: HUBUNGAN SUHU PERMUKAAN LAUT DAN KLOROFIL-A TERHADAP TANGKAPAN TUNA SIRIP KUNING DI PPS CILACAP, INDONESIA - Gimnastiar, Pirgiawan; Dewanti, Lantun Paradhita; Apriliani, Izza Mahdiana; Putra, Pringgo Kusuma Dwi Noor Yadi (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The Cilacap Ocean Fishing Port (PPS) is the main fishing center for yellowfin tuna (Thunnus albacares) in Southern Java. The objectives of this study are to map the distribution of sea surface temperature, chlorophyll-a concentration, and fishing ground for yellowfin tuna in the waters of the Cilacap PPS (Indonesian Fisheries Management Area/WPPNRI 573 and the open sea), and to examine the relationship between sea surface temperature and chlorophyll-a with yellowfin tuna catches. Based on the monthly logbook of the Cilacap PPS for 2019 to 2023, the data used included fishing locations and the number of yellowfin tuna caught. Aqua MODIS Level 3 satellite imagery from the same time period provided information on sea surface temperature and chlorophyll-a. The relationship between sea surface temperature and chlorophyll-a, as well as the catch of yellowfin tuna, was investigated using multiple linear regression in Microsoft Excel 365. The results show that yellowfin tuna were caught between 8–15 °S and 100–112 °E, with the highest catch concentrations occurring between 8–11 °S and 108–111 °E. Sea surface temperature ranged from 25 to 30 °C, while chlorophyll-a concentrations ranged from 0.05 to 0.28 mg/m³. According to the regression model, sea surface temperature and chlorophyll-a combined accounted for only 16% of the variance in catch (R2 = 0.16), indicating that other variables were more important.